A review on the synthetic approaches of rivaroxaban: An anticoagulant drug. Issue 4 (15th April 2017) - Fattah, Tanzeela Abdul; Saeed, Aamer
Graphical abstract: Abstract: Rivaroxaban is an effective and potent oral anti-coagulant drug approved by US FDA in 2008 and is widely used in the treatment of thromboembolic ailments, deep venous thrombosis, pulmonary embolism, myocardial infarction, cerebral stroke, angina pectoris, and transitory ischemic attacks. This review comprehensively provides an overview of the various asymmetric synthetic methods employed for the synthesis of rivaroxaban in high yields and stereoselectivity describing the various chiral synthons used in the synthetic process along with pros and cons of each method. In addition, methods for the industrial production of rivaroxaban have been highlighted in the manuscript.